Level of knowledge about sexually transmitted diseases in young people of the Barrio de Puzo, District of Chilca 2019 - Palomino Hinojosa, Sara (2020)
Objective: To determine the level of knowledge about sexually transmitted diseases in young people of the Barrio de Puzo, District of Chilca 2019. Material and Methods: The study variable is the level of knowledge about sexually transmitted diseases, within the methodology we worked with The scientific method, as it is a logical sequence of procedures, being a basic research of descriptive level, with a population and census sample of 150 young people, ranging between 18 to 29 years with 11 months and 29 days. Results: From 150 (100%) young people surveyed. 94 (62.7%) have a low level of knowledge, 52 (34.7%) have a medium level of knowledge and 4 (2.7%) have a high level of knowledge. The highest percentage of 62.7% is equivalent to 94 young people who have a low level of knowledge about sexually transmitted diseases. Conclusions: It was determined that the level of knowledge about sexually transmitted diseases in young people of the Barrio de Puzo, District of Chilca 2019. It is low with 62.7% equivalent to 94 young people.